Post‐neoadjuvant assessment of tumour budding according to ITBCC subgroups delivers stage‐ and regression‐grade independent prognostic information in intestinal‐type gastric adenocarcinoma. (17th June 2022) - Jesinghaus, Moritz; Herz, Anna‐Lina; Kohlruss, Meike; Silva, Miguel; Grass, Albert; Lange, Sebastian; Novotny, Alexander; Ott, Katja; Schmidt, Thomas; Gaida, Matthias; Hapfelmeier, Alexander; Denkert, Carsten; et al.
Abstract: Tumour budding (TB) has been associated with adverse clinicopathological factors and poor survival in a plethora of therapy‐naïve carcinoma entities including gastric adenocarcinoma (GC). As conventional histopathological grading is usually omitted in the post‐neoadjuvant setting of GC, our study aimed to investigate the prognostic impact of TB in GCs resected after neoadjuvant therapy. We evaluated TB according to the criteria from the International Tumour Budding Consensus Conference (ITBCC) in 167 post‐neoadjuvant resections of intestinal‐type GC and correlated the results with overall survival (OS) and clinicopathological parameters. GCs were categorised into Bd1 (0–4 buds, low TB), Bd2 (5–9 buds, intermediate TB), and Bd3 (≥10 buds, high TB). Carcinomas with intermediate and high TB were significantly enriched in higher ypTNM stages and strongly associated with reduced 5‐year OS in univariable analyses ( p < 0.001). In multivariable analyses including sex, age, resection status, UICC stage, and tumour regression grading, TB remained a stage‐independent predictor of survival ( p < 0.001, hazard ratio Bd2: 2.60, Bd3: 4.74). The assessment of TB according to the ITBCC criteria provides valuable prognostic information in the post‐neoadjuvant setting of intestinal‐type GC and may be a considerable substitute for the conventional grading system in GCs after neoadjuvant therapy.